INTEGRASI MEDIASI KASUS PERCERAIAN DALAM BERACARA DI PENGADILAN AGAMA - Saifullah, Muhammad (Al-Ahkam, 2014)
This research aims to determine the implementation of mediation in divorce cases in The Religion Court Semarang, the substance perspective for PerMA No. 1 of 2008 on Mediation Procedure in the Court, and the legal culture for citizen proposing their problem to the court. This study uses the non-doctrinal law approach that puts the law as "skin out system" or the study of the law in action and also uses doctrinal law approach as a "skin in the system" or the study of law in book, PeMA No. 1 of 2008. The next, the study analysis uses the theory of Lawrence M. Friedman in law enforcement, Lucy V. Kazt theory in the mediation process, and content analysis. The researcher concludes that the mediation in the Religious Courts has not been effective yet because the litigants do not want to make peace, the lack of knowledge about science mediation judge, Religious Court cases are overload and limited means. Besides the existing mediation has just been done in court by requirement in which the parties should attend, whereas this requirement sometimes becomes the mediation success constraints. That is why, the success of mediation must be supported by a legal culture that preceded the dissemination and socialization of justice of peace in the mediation process, prioritybased divorce amicably and based on culture and local wisdom